Sickness Work Personal Reflections of a Sociologist - Nijhof, Gerhard (Springer Singapore, 2018)
This is the story of a professor of Medical Sociology, diagnosed with colon cancer. He undergoes the appropriate medical treatment. Passing through that trajectory, he realizes that things happen that he never read about in the professional literature. During his illness and rehabilitation he scribbles down notes about what is happening to him, what he is observing and what things do not tally with his knowledge of the sociological literature. This continuous connection of personal experience with academic literature is what makes this book such a powerful account of the 'everyday' life of a sick person. Recommended to teachers and students in the field of social health research; to everyone who works in health care, professionals as well as volunteers; and to men and women who themselves are experiencing a serious illness.